Case study of a female ocean racer: Prerace preparation and nutritional intake during the Vendée Globe 2008 - Fearnley, D.; Sutton, L.; O`Hara, J.; Brightmore, A.; King, R. F. G. J.; Cooke, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
The Vendée Globe is a solo round-the-world sailing race without stopovers or assistance, a physically demanding challenge for which appropriate nutrition should maintain energy balance and ensure optimum performance. This is an account of prerace nutritional preparation with a professional and experienced female racer and assessment of daily nutritional intake (NI) during the race using a multimethod approach. A daily energy intake (EI) of 15.1 MJ/day was recommended for the race and negotiated down by the racer to 12.7 MJ/day, with carbohydrate and fluid intake goals of 480 g/day and 3,020 ml/day, respectively. Throughout the 99-day voyage, daily NI was recorded using electronic food diaries and inventories piloted during training races. NI was assessed and a postrace interview and questionnaire were used to evaluate the intervention. Fat mass (FM) and fat-free mass (FFM) were assessed pre- (37 days) and postrace (11 days) using dual-energy X-ray absorptiometry, and body mass was measured before the racer stepped on the yacht and immediately postrace. Mean EI was 9.2 MJ/day (2.4-14.3 MJ/day), representing a negative energy balance of 3.5 MJ/day under the negotiated EI goal, evidenced by a 7.9-kg loss of body mass (FM -7.5 kg, FFM -0.4 kg) during the voyage, with consequent underconsumption of carbohydrate by ~130 g/day. According to the postrace yacht food inventory, self-reported EI was underreported by 7%. This intervention demonstrates the practicality of the NI approach and assessment, but the racer`s nutrition strategy can be further improved to facilitate meeting more optimal NI goals for performance and health. It also shows that evaluation of NI is possible in this environment over prolonged periods, which can provide important information for optimizing nutritional strategies for ocean racing.